The Investigation of the Acceptance of Students Against Microsoft Teams Learning with the SEM-PLS Approach - Denny Nurdiansyah (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
The study aims to determine the accuracy of the expectation-confirmation model and social influence integrated technological acceptance model in predicting the acceptance of student-related online learning with Microsoft Teams. The research design is quantitative research modeling the acceptance of students with SEM-PLS using WarpPLS software. Used primary data collected using a random sampling technique from an online questionnaire for UNUGIRI Statistics students using Microsoft Team until the end of August 2022, using the Likert scale for item questions for the online questionnaire. The result is that obtained implementation of SEM-PLS well with the conclusion that satisfaction, perceived usefulness, and expectation-confirmation significantly affect actual use and continuous intention. In contrast, social influence and perceived ease of use are not significant.